Preliminary study of alkaline direct ethanol fuel cell by using crosslinked quaternized poly (vinyl alcohol)/graphene oxide membrane - Zulfirdaus Zakaria,; Norazuwana Shaari,; Siti Kartom Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A crosslinked of Quaternized Poly (vinyl alcohol)/Graphene oxide (QPVA/GO) composite membrane was prepared via quaternization and solution casting method. With the main objective is to performed lower ethanol permeability membrane than Nafion 117 membrane thus can be the potential alternative membrane in future. The physical and chemical properties of the QPVA/GO membrane were investigated via the Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction analysis (XRD) and Filed Emission Scanning Electron Microscopy (FESEM). The characterization result shows the good interaction of matrix polymer, GO loading and glutaraldehyde as a crosslinked agent. A maximum conductivity of 1.08 × 10-2 S cm-1 was obtained for QPVA/10wt% GO membrane at 30°C. The ethanol permeability has been reduced until 2.2 × 10-7 cm2 s-1 with increasing of 10 wt.% GO loading which was lower than Nafion 117 (19.5 × 10-7 cm2 s-1). The increasing of GO content in composite membranes has append the hydrophobic region which play role as blocking effect to hinder the ethanol crossover. The cell voltage and power density were analyzed at the temperature 30°C. A maximum power density achieved by QPVA/GO membrane was 6.92 mW cm-2 at 10.wt% GO loading which higher than Nafion 117 with only 5.07 mW cm-2 using 2 M ethanol + 2 M KOH at 30°C.